2016
DOI: 10.1371/journal.pone.0157764
|View full text |Cite
|
Sign up to set email alerts
|

Where to Forage in the Absence of Sea Ice? Bathymetry As a Key Factor for an Arctic Seabird

Abstract: The earth is warming at an alarming rate, especially in the Arctic, where a marked decline in sea ice cover may have far-ranging consequences for endemic species. Little auks, endemic Arctic seabirds, are key bioindicators as they forage in the marginal ice zone and feed preferentially on lipid-rich Arctic copepods and ice-associated amphipods sensitive to the consequences of global warming. We tested how little auks cope with an ice-free foraging environment during the breeding season. To this end, we took ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 67 publications
5
46
1
Order By: Relevance
“…The behaviour and energetics of birds may be directly affected by externally attached devices in two primary ways: (1) by expending extra energy countering both the additional mass and the increased drag; and (2) by decreasing some aspects of their performance, such as speed 81 83 . Studies from Spitsbergen and Greenland revealed that little auks equipped with the same type of GPS-logger as in the present study showed longer trip durations 70 , or performed shorter but more frequent long foraging trips 84 compared to unburdened individuals. This bias might have affected the pattern of foraging trips observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The behaviour and energetics of birds may be directly affected by externally attached devices in two primary ways: (1) by expending extra energy countering both the additional mass and the increased drag; and (2) by decreasing some aspects of their performance, such as speed 81 83 . Studies from Spitsbergen and Greenland revealed that little auks equipped with the same type of GPS-logger as in the present study showed longer trip durations 70 , or performed shorter but more frequent long foraging trips 84 compared to unburdened individuals. This bias might have affected the pattern of foraging trips observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…hyperboreus -based energy transfer to C. finmarchicus -based food chain 68 . While adult little auks might be able to cope with suboptimal prey like C. finmarchicus in their environment 69 , the prey selectivity index showed strong preference for breeding birds to provide their chick with large copepods 13 , 70 . Under such conditions, little auks will be forced to search for preferred Arctic prey among very abundant but energetically suboptimal boreal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Seabirds are major consumers of marine biomass, feeding on a variety of fish, cephalopods and crustaceans (Ridoux, 1994;Brooke, 2004). The foraging niche of seabirds is influenced by a range of factors, including environmental conditions (Waugh & Weimerskirch, 2003;Amélineau et al, 2016;Jakubas et al, 2017), prey availability (Baird, 1991;Camprasse et al, 2017), morphological characteristics and their influence on flight performance (Phillips et al, 2004;Phillips, Silk & Croxall, 2005;Navarro et al, 2013), and interspecific competition (González-Solís, Croxall & Afanasyev, 2008;Phillips et al, 2008;Kokubun et al, 2016). Competition is thought to promote foraging niche divergence since species occupying the same ecological niche cannot theoretically coexist through time (Schoener, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…They seemed to avoid shelf waters, potentially because at these locations cold water stemming from the Labrador Current [ 48 ] increased their energy requirements. As in summer, they also targeted the edges of the continental shelf such as around the Grand Banks, where upwelling concentrates prey [ 49 ]. A second wintering strategy was also observed: according to the RSF, there was a medium (January) and high (February) probability of little auk occurrence with medium energy requirements when there was little or no C. finmarchicus ( figure 3 c,d ), which suggests that some of the little auks from East Greenland could rely on different prey/food web at the end of winter.…”
Section: Discussionmentioning
confidence: 99%